The Challenges and Opportunities of Research and Community Service Policies at the Institute for Research and Community Service of UIN Sunan Gunung Djati Bandung and UIN Syarif Hidayatullah Jakarta - Setia Gumilar; Asep Sandi Ruswanda (Publica: Jurnal Pemikiran Administrasi Negara, 2026)
This study analyses the challenges and opportunities of research and community service policy at the Institutes for Research and Community Service (LP2M) of UIN Sunan Gunung Djati Bandung and UIN Syarif Hidayatullah Jakarta. Specifically, it aims to identify the configuration of structural and cultural issues that affect policy implementation, and to map strategic opportunities for strengthening the governance of research and community service in these two State Islamic Higher Education Institutions (PTKIN). The study employs a qualitative approach with a comparative case study design, drawing on in-depth interviews with LP2M stakeholders (chairs, heads of centres, and academic staff), as well as an intensive analysis of national regulatory documents, university statutes, strategic plans, research and community service roadmaps, guidelines and SOPs, and institutional performance and ranking data. Data were analysed thematically to identify policy patterns, constraints, and strategies for reinforcement. The findings show that research and community service policies at both universities have been designed within a relatively comprehensive and integrated framework, with LP2M positioned as a strategic hub for the governance of the Tri Dharma Perguruan Tinggi. However, effectiveness remains constrained by limited funding, disparities in human resource capacity, high academic workloads, administrative bureaucracy, weak global networks, and an academic culture that is not yet fully adaptive. At the same time, the status of both UINs as national reference institutions, regulatory support, the ongoing transformation of PTKIN, digitalisation, and local strengths and strategic networks offer significant opportunities for policy reform and for strengthening research and community service governance in a more effective, inclusive, and socially transformative direction.